1993
DOI: 10.1128/jb.175.11.3459-3467.1993
|View full text |Cite
|
Sign up to set email alerts
|

The plasmid-encoded urease gene cluster of the family Enterobacteriaceae is positively regulated by UreR, a member of the AraC family of transcriptional activators

Abstract: Ureolytic clinical isolates of Providencia stuartii, Salmonella spp., and some Escherichia coli strains contain large urease-encoding plasmids. Expression of urease activity from these isolates is induced at least 20-fold by urea. In order to facilitate studies on the regulatory mechanism controlling this urea-inducible expression, the plasmid-encoded urease genes were inserted into the low-copy-number vector pRK415, to form pSEF70. Deletion mutagenesis of pSEF70 demonstrated that between 1.3 and 1.6 kb of DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 50 publications
1
50
0
Order By: Relevance
“…Although the full sequence of the UPEC ureC gene is not available, phylogenetic analysis of UreA, UreB, and UreG shows that the urease genes of EHEC strains exhibit the highest degree of similarity to those of Klebsiella aerogenes, while the urease genes of UPEC are most similar to those of Proteus mirabilis (data not shown). Furthermore, the gene organizations of the urease operons were different from each other in EHEC and UPEC strains (5). These data suggest that an appropriate primer set can differentiate the EHEC ureC gene from the UPEC ureC gene.…”
mentioning
confidence: 80%
“…Although the full sequence of the UPEC ureC gene is not available, phylogenetic analysis of UreA, UreB, and UreG shows that the urease genes of EHEC strains exhibit the highest degree of similarity to those of Klebsiella aerogenes, while the urease genes of UPEC are most similar to those of Proteus mirabilis (data not shown). Furthermore, the gene organizations of the urease operons were different from each other in EHEC and UPEC strains (5). These data suggest that an appropriate primer set can differentiate the EHEC ureC gene from the UPEC ureC gene.…”
mentioning
confidence: 80%
“…The P. mirabilis urease gene cluster, ureDABCEFG, is induced in the presence of urea and UreR, the transcriptional regulator of the gene cluster (D'Orazio & Collins, 1993D'Orazio et al, 1996;Island & Mobley, 1995;Nicholson et al, 1993). P. mirabilis UreR, a dimer of 33?4 kDa polypeptides is an AraC-like transcriptional regulator that activates transcription from p ureD and p ureR in a urea-inducible manner (D'Orazio et al, 1996;Island & Mobley, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the deduced amino acid sequence of the ORF with sequences in the GenBank database showed that the protein possesses a distinct primary sequence similarity to UreR and AraC (19 and 22% identity, respectively). This homology was essentially confined to the C-terminal sequence of each locus, especially in the amino acids that characterize the C-terminal DNA binding region for the AraC family of DNA binding proteins (6) (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%